2020
DOI: 10.1097/ccm.0000000000004256
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment of the Percutaneous Electrical Phrenic Nerve Stimulation System in Patients on Mechanical Ventilation

Abstract: Objectives: Maintaining diaphragm work using electrical stimulation during mechanical ventilation has been proposed to attenuate ventilator-induced diaphragm dysfunction. This study assessed the safety and feasibility of temporary percutaneous electrical phrenic nerve stimulation on user-specified inspiratory breaths while on mechanical ventilation. Design: Two-center, nonblinded, nonrandomized study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
(2 reference statements)
1
34
0
Order By: Relevance
“…It was proven to be associated with a higher rate of mechanical ventilation weaning failure and prolonged length of mechanical ventilation (52). Upon this condition, we also included electrical stimulation of phrenic nerve to minimize the reduction of diaphragm atrophy and strength over time, possibly contributing to speed up respiratory functional recovery and subsequently leading to increased rate of ECMO weaning and shortened length of ECMO therapy (53)(54)(55). Taken together, it is reasonable to hypothesize that our protocolized cardiopulmonary rehabilitation may contribute to internal pathophysiological changes (e.g., cardiac output and maximal oxygen uptake) and spread it to external clinical outcomes (e.g., earlier weaning of ECMO and increased rated of ECMO weaning).…”
Section: Discussionmentioning
confidence: 99%
“…It was proven to be associated with a higher rate of mechanical ventilation weaning failure and prolonged length of mechanical ventilation (52). Upon this condition, we also included electrical stimulation of phrenic nerve to minimize the reduction of diaphragm atrophy and strength over time, possibly contributing to speed up respiratory functional recovery and subsequently leading to increased rate of ECMO weaning and shortened length of ECMO therapy (53)(54)(55). Taken together, it is reasonable to hypothesize that our protocolized cardiopulmonary rehabilitation may contribute to internal pathophysiological changes (e.g., cardiac output and maximal oxygen uptake) and spread it to external clinical outcomes (e.g., earlier weaning of ECMO and increased rated of ECMO weaning).…”
Section: Discussionmentioning
confidence: 99%
“…The above findings collectively indicated that the electrode placement procedure and the associated stimulation protocol would be transferable to humans in a clinical setting. The results of this GLP study served as the basis for developing the clinical protocol for the recently completed PEPNS first-in-human clinical study [6].…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent electrical stimulation of the phrenic nerves to pace the diaphragm has been suggested as a strategy to minimize the reduction in diaphragm atrophy and to potentially reduce weaning failure [2]. Recently, O'Rourke et al demonstrated the ability to safely and successfully place percutaneous multipolar leads in the anatomical region of the neck close to phrenic nerves in patients on mechanical ventilation and to use these leads to deliver percutaneous electrical phrenic nerve stimulation (PEPNS) [6]. The authors reported that they were able to demonstrate the feasibility of using this approach to synchronize electrical stimulation with inspiration while maintaining Work of Breathing (WOB) within defined limits.…”
Section: Stimulation Of the Phrenic Nerves To Induce Diaphragmatic Momentioning
confidence: 99%
“…Diaphragm protective ventilation can prevent diaphragm atrophy, compared with lung protective ventilation [ 58 ]. Furthermore, O’ Rourke et al reported that percutaneous electrical phrenic nerve stimulation increased diaphragm thickness by 15.1% within 48 h [ 59 ]. Extracorporeal support is also considered to prevent diaphragm injury [ 60 ], and in a case report, the early initiation of extracorporeal support prevented diaphragm atrophy, with a relatively suppressed level of urinary titin N-fragment of 24.1–38.4 pmol/mg Cr [ 61 ].…”
Section: Muscle Atrophymentioning
confidence: 99%